CONTEXTUAL TEACHING AND LEARNING (CTL) IN OFFLINE SETTINGS: ENHANCING BUSINESS ENGLISH FLUENCY FOR WOMEN ENTREPRENEURS THROUGH REAL-WORLD SCENARIOS - Muthmainnah Bahri A. Bohang; Aqzhariady Khartha; Heri Alfian; Marhamah Marhamah; Bimas Reskiawan; Hustiana Hustiana; Sri Hariati Mustari (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
This study investigated the effectiveness of Contextual Teaching and Learning (CTL) in enhancing business English fluency among 30 Women micro-entrepreneurs in Makassar, Indonesia, through offline simulations of real-world business scenarios. A mixed-methods approach was employed, combining pre/post-tests (modified IELTS Speaking Test) with qualitative data from interviews and observations to assess improvements in linguistic proficiency and confidence. Participants engaged in eight sessions of CTL-based activities, including negotiation role-plays, product presentations, case studies, and collaborative proposal writing, aligned with Kolb’s Experiential Learning Theory and ESP principles. Quantitative results revealed significant gains: mean IBECT scores increased from 5.2 to 7.0 (Cohen’s d = 1.46, large effect), while self-reported confidence rose by 35% (p < 0.05). Qualitative insights highlighted enhanced critical thinking and strategic negotiation skills through simulations (e.g., adapting to non-verbal cues, tactical decision-making) and vocabulary expansion via peer collaboration. However, time constraints in role-plays were noted as a challenge, albeit fostering adaptability under pressure. Despite limitations such as a small sample and short intervention period, the findings underscored CTL’s potential to bridge theoretical knowledge and practical application, offering actionable strategies for inclusive, context-specific training programs. The study recommended flexible practices—like dual-role-play formats—to balance realism and pedagogical depth, ultimately empowering women entrepreneurs in global business contexts.